Implementation of the Apostle Paul’s Teaching on Love Based on 1 Corinthians 13:1–13 for Sunday School Children Aged 7–12 - rini; Sriwahyuni; Bambang Setiadi Ananius (Gereja Alkitab Anugerah Kadoudan, 2025)
This study investigates the implementation of the Apostle Paul’s teaching on love based on 1 Corinthians 13:1–13 among Sunday School children aged 7–12 years at Bethel Tabernacle Church of Christ Alpha Omega Temahar, Landak, West Kalimantan. The research addresses the discrepancy between the theological teaching of love and its observable application in children’s daily attitudes and behaviors. A quantitative research design was employed using a Likert-scale questionnaire administered to 26 respondents. Data were analyzed using SPSS 25 through validity and reliability testing, normality testing, confidence interval analysis, linear regression, and one-way ANOVA at a 5% significance level. The findings indicate that the overall implementation of Paul’s teaching on love is classified at a moderate level, as reflected in a confidence interval ranging from 140.8919 to 149.6466. Among the examined dimensions, the Action of Love (D2) emerged as the most influential factor, demonstrating a strong correlation (r = 0.915) and a coefficient of determination of 0.838, accounting for 83.8% of the variance. The study concludes that while the teaching of love has been moderately implemented, greater emphasis on practical expressions of love is essential. These results provide empirical support for strengthening action-oriented Christian character education for children.